Uncovering multi-level mental healthcare barriers for migrants: a qualitative analysis across China, Germany, Netherlands, Romania, and South Africa - Alina Ioana Forray; Ovidiu Oltean; Saskia Hanft-Robert; Rowan Madzamba; Andrian Liem; Barbara Schouten; Christine Anthonissen; Leslie Swartz; Răzvan Mircea Cherecheș; Sanna Higgen; Brian J. Hall; Mike Mösko (BMC, 2024)
Abstract Background Forced displacement is a significant issue globally, and it affected 112 million people in 2022. Many of these people have found refuge in low- and middle-income countries. Migrants and refugees face complex and specialized health challenges, particularly in the area of mental health. This study aims to provide an in-depth qualitative assessment of the multi-level barriers that migrants face in accessing mental health services in Germany, Macao (Special Administrative Region of China), the Netherlands, Romania, and South Africa. The ultimate objective is to inform tailored health policy and management practices for this vulnerable population. Methods Adhering to a qualitative research paradigm, the study centers on stakeholders' perspectives spanning microsystems, mesosystems, and macrosystems of healthcare. Utilizing a purposive sampling methodology, key informants from the aforementioned geographical locations were engaged in semi-structured interviews. Data underwent thematic content analysis guided by a deductive-inductive approach. Results The study unveiled three pivotal thematic barriers: language and communication obstacles, cultural impediments, and systemic constraints. The unavailability of professional interpreters universally exacerbated language barriers across all countries. Cultural barriers, stigmatization, and discrimination, specifically within the mental health sector, were found to limit access to healthcare further. Systemic barriers encompassed bureaucratic intricacies and a conspicuous lack of resources, including a failure to recognize the urgency of mental healthcare needs for migrants. Conclusions This research elucidates the multifaceted, systemic challenges hindering equitable mental healthcare provision for migrants. It posits that sweeping policy reforms are imperative, advocating for the implementation of strategies, such as increasing the availability of language services, enhancing healthcare providers' capacity, and legal framework and policy change to be more inclusive. The findings substantially contribute to scholarly discourse by providing an interdisciplinary and international lens on the barriers to mental healthcare access for displaced populations.